Changes in the blood parameters of the Amazonian manatee (Trichechus inunguis) after long-distance transportation - doi: 10.4025/actascibiolsci.v35i4.20081 - Carmo, Talita Laurie Lustosa do; Amaral, Rodrigo de Souza; Rosas, Fernando Cesar Weber; d’Affonsêca Neto, José Anselmo; Reisfeld, Laura; Silva, Vera Maria Ferreira da (Acta Scientiarum. Biological Sciences, 2013)
In this study we report the hematological, biochemical and hormonal parameters in a juvenile male Amazonian manatee measured before transport, immediately after transport, and during adaptation to a new facility. The animal was transported from Manaus, Amazonas, Brazil, to São Paulo, São Paulo, Brazil, (2,733 km) within 6 hours. Among all blood parameters analyzed, we observed obvious neutrophilia, lymphopenia, and increases in the neutrophil/lymphocyte ratio and serum glucose and aspartate aminotransferase (AST) levels, but these parameters subsequently returned to normal. These results suggest that transport and changes in the environment are temporary stressful events for Amazonian manatees. We, therefore, recommend monitoring the hematological and biochemical parameters before and after translocation to minimize the effects of handling stressors in this species